The Qur'an: the basics - Campanini, Massimo (The Basics, 2007)
This highly topical new introduction to the holy book of Islam includes essential reference resources such as a chronology of the revelation, web links and extensive guides to further reading. Exploring the Qur'an's reception through history, its key teachings and its place in contemporary thought and belief, the book analyzes: The Qur'an as the word of God; its reception and communication by the Prophet Muhammad; the structure and language of the text; conceptions of God, the holy law and jihad; and Islamic commentaries on Qur'anic teachings through the ages. "Qur'an: The Basics" is a concise and easy to read introduction to text that provides the foundations of Muslim faith, right-living and daily worship.